Capital Structure and Corporate Performance of Indonesian Building Construction Sub Sector - Suciati, Ranila (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the effect of Capital structure on the Financial Performance of Indonesian building construction sub sector. This research was conducted with the aim of analyzing capital structure and financial performance during 2015 to 2018 (4 years). For the purpose of this study, data were processed from a sample of annual reports of Indonesian Building Sub Sector companies listed on the Indonesia Stock Exchange. The analytical method used is panel data regression, will reveal the relationship between capital structure and financial performance with a significance level of 0.05. Research results for construction and building sub sector companies in Indonesia The R square value of this model is 0,30 which means that variations of Corporate Performance that can be explained by the independent variables analyzed are DER, DAR, and LTDC by 30.02 percent and the remaining 69.98 percent explained by other factors not included in this study.